2009
DOI: 10.1007/s11085-008-9134-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium Content on the Oxidation Behaviour of Ferritic Steels for Applications in Steam Atmospheres at High Temperatures

Abstract: Environments containing water vapour are common in many industrial processes, such as power generation systems. Hence, long-term oxidation (1000 h) of P-91 and AISI 430 was studied at 650 and 800°C, in 100% H 2 O atmosphere. The oxidation resistance of the AISI 430 is better than that of the P-91, due to the formation of protective phases on the surface. At 650°C, a scale composed of Fe 3 O 4 , Fe 2 O 3 and (Fe,Cr) 3 O 4 is formed on P-91, although at 800°C the scale is mainly composed of Fe 3 O 4 and (Fe,Cr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Shibli and Starr [32] indicated that 10-11 % of chromium in material allows the protective, external chromia (Cr 2 O 3 ) to be formed; on the other hand Sanchez et al [31] have shown that such level suppose to be around 11-12 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shibli and Starr [32] indicated that 10-11 % of chromium in material allows the protective, external chromia (Cr 2 O 3 ) to be formed; on the other hand Sanchez et al [31] have shown that such level suppose to be around 11-12 %.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced impact of Cr is a result of slower diffusion of metal ions at 600°C as the diffusion coefficients are temperature dependent [29,30]. It could be also explained as a result that neither of those two steels has sufficient amount of chromium which can effectively suppress the non-protective oxide growth at higher temperatures [31].…”
Section: Discussionmentioning
confidence: 99%
“…A number of modified 9-12 % Cr ferritic/martensitic steels with higher creep strength have been developed and are currently being used for critical components in coal-fired power plants such as heat exchangers, headers, steam lines and exhaust gas systems [5][6][7]. Although these steels have excellent oxidation resistance during exposure in oxygen or air [7], their oxidation rates are significantly enhanced in environments containing water vapour as those prevailing in power plant service conditions [6][7][8][9][10][11][12][13]. Therefore, superheater tubes of modified 9-12 % Cr steels are limited for use up to a maximum working temperature of 620°C in the air-fired power plants due to their limitations to oxidation and creep [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…7 Both oxidation kinetics and the scale morphology are reported to be strongly dependent on the steel composition, surface finish and test conditions: metal temperature, steam flow and chemistry. 8 Among highlighted factors, chromium levels are of crucial importance 9 ; however, levels seems to have less impact below 570°C. Therefore for components operating at temperatures below 570°C the steels with lower Cr levels may be employed.…”
Section: Introductionmentioning
confidence: 99%
“…Shibli and Starr 11 indicated that in temperature range of 600-650°C, 10-11% of chromium in the base metal allows protective, external chromia (Cr 2 O 3 ) to be formed; in contrast Sanchez et al 9 have shown that such an oxide forming with Cr content greater than 11-12% for steels exposed to steam at temperatures above 600°C. Quadakkers et al 12 concluded that the scale formed on ferritic and austenitic steels differs with the chromium content in the base material; it is recognised that scale changes in following manner: with increasing Cr content it changes from haematite/magnetite to magnetite/(Fe, Cr) 3 Viswanathan et al 6 proposed the following ranking of the high-temperature resistant steels, due to their chromium levels and their relation with protective properties of the scale: IN740, Haynes 230, HR120, HR6W, HR3C, TP347HFG, Super 304H, T92, T91 and finally T23.…”
Section: Introductionmentioning
confidence: 99%